Learning Social Sciences as a Means for Forming Student Character in Facing the Industry 4.0 Revolution - Gallih Arya Mulyadi; Firman Firman; Rusdinal Rusdinal (Journal of Counseling, Education and Society, 2020)
The changing times and technological developments are so fast that they change from all walks of life. These changes and terms are the industrial revolution 4.0 that we are often hearing about. This era of access to information and everything is very easy to obtain. For that we need personalities and characters who are able to be adaptive and able to survive the changing times. This industrial revolution also changes the economic, social and political patterns in our environment. No exception is also changing our education patterns. There is an e-learning pattern that forces our students to participate immediately and be adaptive to it. But there is an irony in addition to the development of this era is that not all students are able and can immediately adapt to this internet pattern. Most even abuse the freedom of access and then access the internet at this time. In fact, it becomes a weakness for us in the future, they are complacent and even cool in cyberspace and unable to socialize well in the real world. For this reason, student character education is needed, namely by learning social science. No less important is the synergy between parents, schools, teachers and the community to make the nation's successor students able to face and compete in the industrial era 4.0